Determination of the minimum number of plants and the minimum area to be harvested for correct crop yield determinations - Hauser, Stefan; Saito, Kazuki (2023)
To correctly express the yield of any crop, it is of paramount importance to correctly determine the surface area from which the crop is harvested. The determination of the minimum harvest area is connected to the plant density and thus the minimum number of plants that would need to be harvested to attain repeatable results. This standard operating procedure (SOP) is separated into three modules to accommodate the wide range of plant densities of the relevant crops. The first module is on crops sown or planted at high density (usually > 20 plants or hills/m2), such as cereals (rice, wheat, barley), small-seeded pulses and certain oil seeds. The second module is on large cereals such as maize and sorghum and most root and tuber crops such as cassava, sweet potato, potato and yam, which are sown or planted at medium densities ranging from around 1 to 20 plants or hills/m2. The third module is on perennials such as banana and plantain, and on tree crops such as cocoa and coffee, which are planted at low densities and where individual plants may be assessed rather than whole plant populations.